L’emergenza Coronavirus tra Stato e Regioni: alla ricerca della leale collaborazione (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The problematic relationship between State and Regions in the Coronavirus crisis is one of the most controversial and discussed issues, even in public debate. The paper aims at investigating the main reasons for such a conflicting relation. The legal framework of crisis management is examined by underlining how the existing rules were substantively changed by the decree-laws no. 6 and no. 19 of 2020. The result is a marginalization of the role of the Regions. The conclusion is that it is urgent to recover the constitutional principle of loyal cooperation and to re-activate the so-called “Conference system”.
Keywords: CoViD-19; pandemic emergency; crisis management; State and Regions; loyal cooperation